Rancang Bangun Arsitektur Microservices untuk Massive Open Online Courses (Universitas Bengkulu, 2025)
The advancement of information technology has revolutionized learning, enabling remote teaching with flexible schedules. MOOCs, a new learning model, offer accessible education anytime, anywhere, with no participant limits. In developing MOOCs, microservices architecture can be applied, as shown in the Vocasia.id case study, which includes services like authentication, catalog, course, email, enrollment, finance, instructor, order, and payment using business capability decomposition. Docker is used for containerization to ensure application portability, while Kubernetes handles orchestration for efficient deployment and scaling. Benchmarking identifies optimal configurations, with maximum CPU usage reaching 28 cores and memory usage at 13 GiB. To ensure system stability, a horizontal pod autoscaler is configured with a 60% target for CPU and memory usage, supporting a minimum of 2 pods and a maximum of 5 pods.